2014
DOI: 10.1179/2045772314y.0000000273
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of the Buyang Huanwu decoction on functional recovery in rats following spinal cord injury

Abstract: Background: The Buyang Huanwu decoction (BYHWD) is a traditional Chinese herbal prescription and has been used in China to treat spinal cord injury (SCI) for hundreds of years. Clinical trials have shown that BYHWD improves the outcome of SCI in clinical trials, but the mechanisms are not known. This study observed the neuroprotective effects of BYHWD on spinal nerve cells after SCI and investigated possible mechanisms. Materials and methods: Forty female Wistar rats were randomized equally to four groups trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Buyang Huanwu Decoction (BYHWD) is a 7-herb Chinese herbal formation consisting of Astragalus membranaceus , Angelica sinensis , Paeonia lactiflora , Ligusticum chuanxiong , Prunus persica , Carthamus tinctorius and Lumbricus terrestris . The formulation is widely used for treating ischemic and neurodegenerative diseases [ 105 , 106 ]. Results from pervious clinical studies have shown that BYHWD improved neurological functions in cerebral infraction patients, which has been suggested to be associated with an increased serum VEGF expression [ 107 ].…”
Section: Angiogenic Effects Of Chinese Herbal Medicine In Ischemicmentioning
confidence: 99%
“…Buyang Huanwu Decoction (BYHWD) is a 7-herb Chinese herbal formation consisting of Astragalus membranaceus , Angelica sinensis , Paeonia lactiflora , Ligusticum chuanxiong , Prunus persica , Carthamus tinctorius and Lumbricus terrestris . The formulation is widely used for treating ischemic and neurodegenerative diseases [ 105 , 106 ]. Results from pervious clinical studies have shown that BYHWD improved neurological functions in cerebral infraction patients, which has been suggested to be associated with an increased serum VEGF expression [ 107 ].…”
Section: Angiogenic Effects Of Chinese Herbal Medicine In Ischemicmentioning
confidence: 99%
“…In the last two years, many research studies, focusing on the identification of drugs potentially effective in SCI treatment, have been published [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ,…”
Section: Overview Of Current Pharmacological Approaches For the Trmentioning
confidence: 99%
“…Recent experimental studies have shown promising results, indicating BHD's effectiveness in treating SCI, peripheral nerve injury, stroke, facial nerve palsy, cerebral ischemia, and vascular dementia. [7][8][9][10] Through various experimental models, BHD has demonstrated its ability to enhance neurogenesis and neuroprotection via multicompound and multi-signaling pathways. [6][7][8][11][12][13] Additionally, BHD has shown potential in promoting spinal cord repair in animal models, influencing the micro-environment post-SCI in rats, preventing neuronal death and atrophy, promoting axonal regeneration, and facilitating functional recovery of limbs.…”
Section: Introductionmentioning
confidence: 99%